2008
DOI: 10.1292/jvms.70.1359
|View full text |Cite
|
Sign up to set email alerts
|

Mice are Not Susceptible to Hepatitis E Virus Infection

Abstract: ABSTRACT. To determine whether or not mice are susceptible to hepatitis E virus (HEV) infection, C57BL/6 mice were experimentally infected with genotypes 1, 3 and 4 HEV by intravenous injection. Serum and stool samples were collected and used to detect HEV RNA and anti-HEV antibodies by RT-PCR and ELISA. The virus infection was monitored up to two months after inoculation; however, none of the serum or stool samples was positive for virus replication, demonstrating that C57BL/6 mice were not susceptible to HEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Trials to experimentally infect laboratory rats or mice with human HEV led to contradictory results, because some studies reported successful infection and others did not. 27,28 Recently, an HEV-related agent was detected from wild rats, and sequence comparison to human and avian HEV strains revealed only 59.9% and 49.9% nucleotide identity, respectively. 29 The low nucleotide sequence identities between rat HEV and human HEV may indicate an independent evolution of both viruses with no transmission between both hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Trials to experimentally infect laboratory rats or mice with human HEV led to contradictory results, because some studies reported successful infection and others did not. 27,28 Recently, an HEV-related agent was detected from wild rats, and sequence comparison to human and avian HEV strains revealed only 59.9% and 49.9% nucleotide identity, respectively. 29 The low nucleotide sequence identities between rat HEV and human HEV may indicate an independent evolution of both viruses with no transmission between both hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Trials to infect laboratory rats or mice experimentally with human HEV led to contradictory results, as some studies reported successful infection whilst others did not (Karetnyï et al, 1993;Li et al, 2008;Maneerat et al, 1996). Several studies have shown the detection of HEV-specific antibodies in rodents from different countries including India, Vietnam, Brazil, Japan and the USA, including commensal rodents such as Norway (Rattus norvegicus) and black (Rattus rattus) rats, but also wild rodents such as deer mouse (Peromyscus maniculatus) and cotton rat (Sigmodon hispidus) (Arankalle et al, 2001;Favorov et al, 2000;Hirano et al, 2003;Kabrane-Lazizi et al, 1999;Meng et al, 2002;Vitral et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…HEV-specific antibodies as well as viral RNA have been detected in several animal species (Smith, 2001;Meng, 2009 An initial indication for a potential role of rodents in the transmission of hepatitis E was found by the detection of HEV antigen in the sera of rodents caught next to a Russian village where an outbreak of hepatitis E was reported (Karetnyï et al, 1993). Trials to infect laboratory rats or mice experimentally with human HEV led to contradictory results, as some studies reported successful infection whilst others did not (Karetnyï et al, 1993;Li et al, 2008;Maneerat et al, 1996). Several studies have shown the detection of HEV-specific antibodies in rodents from different countries including India, Vietnam, Brazil, Japan and the USA, including commensal rodents such as Norway (Rattus norvegicus) and black (Rattus rattus) rats, but also wild rodents such as deer mouse (Peromyscus maniculatus) and cotton rat (Sigmodon hispidus) (Arankalle Favorov et al, 2000;Hirano et al, 2003;Kabrane-Lazizi et al, 1999; Meng et al, 2002;Vitral et al, 2005).…”
mentioning
confidence: 99%
“…However, antibody titers were lower and less lasting than those previously observed after vaccination with baculovirus-expressed proteins (18). Although HEV has recently been detected in rats with shedding of virus (21,23,37), and HEV experimental infection has been reported with nude mice (15), HEV does not seem to infect immunocompetent mice (26); therefore, the protective capacity of the immunological status acquired by these animals after vaccination with the recombinant vaccinia viruses was not evaluated.…”
Section: Discussionmentioning
confidence: 99%